The German employment protection act: How does it work in company practice? - Karen Ullmann; Silke Bothfeld (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2008)
The article describes the manner in which in companies make decisions about dismissals. It begins with the presentation of a number of theories, which attempt to depict the complexity of the employment relationship. This is followed by the presentation of the legal framework and the various options for action at the respective levels. The third section draws together empirical data that illuminates the relevance of the various steps involved in the termination of the employment relationship. It shows that the prevalent assumptions that companies hold regarding the effects of the KSchG are unfounded.
Keywords: 330; Employment Protection Legislation; Dismissal; Severance Payment; Arbeitnehmerschutz; Kündigungsschutz; Abfindung; Theorie; Deutschland